Folha da esperança: trajetória e perspectivas da Liga Canábica da Paraíba - Silva Junior, Josemar Elias da (2019)
It regards to the struggled trajectory of Liga Canábica da Paraíba, a non-profit association founded by a group of parents and relatives of children with hard to contain epilepsy, which militates daily to achieve a national policy for medical cannabis and thus provide a better quality of life for their families through out the therapeutic benefits found in the plant’s components. The trajectory was built considering what Bourdieu (1996) advocates, that the subject or even institution is fractal and travels several places in the social enviroment. Thus, one does not assume aspects of biography in which the history is brought in a linear way. In this way, we have as main source for data gathering the League’s documents files, until now unexplored and considered by us a source of limitless memories and information - capable of revealing aspects of the progress of this association in space and time. The concept of guiding memory for the construction of the trajectory is the one adopted by Thiesen (2013), that brings the so called institutional memory, capable of covering the past testimony of the institution's emergency period (2014) when it was not yet a formal association until the present estructure as the Liga Canábica da Paraíba. As a methodological mechanism, we used qualitative research associated with conducting interviews with the leaders of the League - Júlio Américo and Sheila Geriz – intending to validate information in the documents selected for the research. The documents were analyzed considering the actions that caused them and taking their memorialist aspects and sociocultural value, using the documentary analysis technique of Aróstegui (2006). In this way, the information that is presented in its archives, associated to the memory mechanism, with the help of the oral narratives of its leaders, we managed to reveal the existence of a social institution in constant action, that runs through several spheres of power, among them: social, political, educational and medicinal; seeking to disseminate reliable information about the beneficial medicinal effects of the use of cannabis sativa components such as CBD and THC. Thus, their dynamics routinely involves struggle, love, acceptance, companionship and resistance regarding the search for a public policy focused on medical cannabis and subversion of prejudice associated with the plant and extended to those who make use of it.